End of life decisions in the case of incompetent and terminally ill children under Spanish Law (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
This article addresses the Spanish constitutional and legal framework of end of life decisions especially with regard to incompetent and terminally ill children.
Keywords: Fundamental rights to life and to personal integrity; informed consent; terminally ill patients; incompetent patients; minor patients